1989
DOI: 10.1002/bjs.1800760929
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative colonic irrigation in the treatment of acute sigmoid volvulus

Abstract: activities are acceptable. For stage I ingrowing toenails the combination of conservative measures studied was shown t o be successful. In cases of stage I1 ingrowing nails, success can also be achieved but recurrences are frequent in the long term

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…This study showed no statistically significant association between age and outcome (p=0.308) and is in keeping with findings from another study by Jumbi et al, 2008. Many studies from the West have shown that increasing age and co-morbidity affects outcome 18,19 . In the Western population the mean age of presentation with acute sigmoid volvulus is 62-78 years whilst in the African population it is 42-55 years 14 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study showed no statistically significant association between age and outcome (p=0.308) and is in keeping with findings from another study by Jumbi et al, 2008. Many studies from the West have shown that increasing age and co-morbidity affects outcome 18,19 . In the Western population the mean age of presentation with acute sigmoid volvulus is 62-78 years whilst in the African population it is 42-55 years 14 .…”
Section: Discussionsupporting
confidence: 89%
“…Earlier studies had reported a mortality of 58% and 37% respectively 38,39 . Madiba et al, in South Africa also reported a high mortality of 30% 14 as have other studies in different parts of the world showed a higher mortality rate following emergency resection compared to elective resection 14,18 .…”
Section: Serum Electrolyte Levelsmentioning
confidence: 66%
See 3 more Smart Citations